Worldwide unintentional acute pesticide poisonings: reassessing the occupational and non-occupational burden - Wolfgang Boedeker; Meriel Watts; Peter Clausing; Emily Marquez (Frontiers in Public Health, 2026)
Background Human poisoning by pesticides has long been seen as a severe public health problem. As early as 1990, a task force of the World Health Organization (WHO) estimated that about one million unintentional pesticide poisonings occur annually, leading to approximately 20,000 deaths. In 2020, a systematic review found that about 385 million cases of unintentional, acute pesticide poisoning (UAPP) were occurring every year. Our aim is to update the annual global estimate of UAPP, based on a systematic review of available data. Methods We updated the existing systematic review of the scientific literature to include the period from 2006 to 2023 supplemented by mortality data from WHO. We extracted data from publications and the WHO Mortality Database, then performed country-wise synopses, and arrived at annual numbers of national UAPP. World-wide UAPP was estimated based on national figures and population data for worldwide regions. We conducted a sensitivity analysis to illustrate the effects of different study designs on the global estimate. Results In total 139 countries were covered, including 62 countries covered by 214 articles from 2006 to 2023, and an additional 77 countries covered by data from the WHO Mortality Database. Approximately 369,632 annual cases of UAPP were reported by the extracted publications, resulting from 9,182 fatalities and 360,450 non-fatal cases. On this basis, we estimate that about 402 to 433 million cases of UAPP occur annually worldwide, including around 11,000 fatalities. Based on a worldwide farming population of approximately 934 million, this means that an estimated 46% of farmers are being poisoned by pesticides every year. The greatest estimated number of non-fatal UAPP cases is in southern Asia, followed by south-eastern Asia and east Africa. Conclusion Along with other estimates, robust evidence is presented that acute pesticide poisoning is an ongoing major global public health challenge. There is an urgent need to recognize the high burden of non-fatal UAPP, particularly on farmers and farmworkers. The implementation of the recommendation by the Council of the Food and Agriculture Organization of the United Nations (FAO), to phase out highly hazardous pesticides (HHPs) could significantly reduce the burden of UAPP.